Pathways Awareness’s Brochure As Early Detection for Child Development - Nursalam Nursalam; Ilya Krisnana; Nantiya Pupuh Satiti (Jurnal Ners, 2009)
Introduction:Parental awareness of the earliest milestones considerably lower than of the later milestones. To raise parental awareness, Pathways Awareness’ brochure (PAB) can be used by the parents. The objective of this study was to examine the effect of health education of Pathways Awareness’ brochure to the behavior of parental early identification in child (3-15 months) early development.Methods: This study used Quasy-Experimental design. Population had taken from parents who have a child from 3 until 15  months. Sample was comprised in to 30 individuals who fit with the inclusion criteria. Sample was divided by two groups, one group as intervention group, and another one as control group. The independent variable in this study were health education of Pathways Awareness’ brochure. The dependent variable was the behavior of parental early identification in child (3-15 months) early development. Data was collected by questionnaire of family knowledge, family attitude, and family action. They were analyzed by Wilcoxon Signed Rank Test with significance level  α<0.05.Results: According to the result by Wilcoxon Signed Rank Test, there was a significance difference between the behavior of parental early identification in child (3-15 months) early development before and after the intervention ( family knowledge p = 0,003; family attitude p = 0,034; family action p = 0,025).Analysis:It conclusion, pathway awarness’  brochure foster the behavioural of the parents on early detection.Conclusion: It is recommended to explore study on cooperation of PAB and KMS.